La théorie post-keynésienne et la recherche empirique - Eichner, Alfred (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractThe paper argues that post-Keynesian theory has reached a third stage in its development, that of empirically validating its arguments. The failure of the alternative neoclassical paradigm to meet any of the necessary empirical tests — the correspondence, comprehensiveness, parsimony and praxis tests in particular — is first pointed out. The methodological pitfalls which post-Keynesian theory must guard against if it is to avoid the same result are then indicated. From this line of argument emerges the imminent research agenda if post-Keynesian theory is eventually to place economics on a scientific basis by developing a body of theory which can be both empirically validated and conducive to further empirical research.